(untitled) (Research, Society and Development, 2022)
Land use and occupation by agriculture and urbanization generate several impacts on the natural environment and water quality in a watershed is the main parameter capable of reflecting the consequences of anthropogenic activities that occur in this location. Protecting water resources and their tributaries is of utmost importance for the preservation of the nature and health of the population in relation to direct and indirect consumption of water. In this sense, objectified with this research was to analyze the water quality for consumption and bathing in springs (N1, N2, N3, N4, N5 and one outfall, Foz),) with different soil cover in the Rio Grande watershed. Water collections were performed monthly over a period of one year and physical, chemical and bacteriological parameters were evaluated. The data obtained were submit to statistical analysis and the results showed that the sources N1 and N2 had the lowest values in turbidity, color, biological oxygen demand (BOD) and pH, being the latter very close to neutrality. The spring N3 in relation to the others, presented lower values for temperature and dissolved oxygen. N1 indicated having the best water quality values for the physical and chemical parameters. All springs and outfall presented some type of bacteriological contamination and the risk to the population using these waters. Finally, the results show that the presence of vegetation around the water resources influences in the water quality of the springs.